Tim f(x) biet
F(x) + F(\(\frac{1}{2}\)) + F(\(\frac{1}{13}\)) =26x + 24
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(f\left(7\right)=\frac{7+2}{7-1}=\frac{9}{6}=\frac{3}{2}\)
b)
\(f\left(x\right)=\frac{1}{4}\Rightarrow\frac{\left(x+2\right)}{x-1}=\frac{1}{4}\)
dk \(x\ne1\Leftrightarrow4.\left(x+2\right)=x-1\Leftrightarrow4x+8=x-1\Rightarrow x=-3\)
c)
\(f\left(x\right)>1=>\frac{x+2}{x-1}>1\Leftrightarrow\frac{\left(x+2\right)-\left(x-1\right)}{x-1}>0\)
\(\Leftrightarrow\frac{3}{x-1}>0\Leftrightarrow x-1>0\Rightarrow x>1\)
\(\frac{11}{8}+\frac{13}{6}=\frac{85}{x}\)
\(\frac{85}{24}=\frac{85}{x}\)
\(x=24\)
\(2x-\frac{2}{11}=1\frac{1}{5}\)
\(2x-\frac{2}{11}=\frac{6}{5}\)
\(2x=\frac{76}{55}\)
\(x=\frac{38}{55}\)
a. \(\frac{11}{8}\)+ \(\frac{13}{6}\)= \(\frac{85}{x}\)
\(\frac{85}{24}\) =\(\frac{85}{x}\)
x = \(\frac{24\cdot85}{85}\)
x = 24
b. 2x - \(\frac{2}{11}\)=1\(\frac{1}{5}\)
2x- \(\frac{2}{11}\)= \(\frac{6}{5}\)
2x = \(\frac{6}{5}\)+\(\frac{2}{11}\)
x = \(\frac{76}{55}\): 2
x = \(\frac{38}{55}\)
Học tốt nha ~~~~~ ỌvỌ